VD_FINDINFO AP / 2009 / 71 vom 10. Juni 2008 - VD Tribunal cantonal (2008)
DROIT DU TRAVAIL, RÉSILIATION ABUSIVE, INDEMNITÉEN GÉNÉRAL, INDEMNITÉ DE VACANCES | 329d al. 2 CO, 335 al. 1 CO, 336 al. 1 let. d CO, 336a al. 1 CO, 336a al. 2 CO, 42 al. 2 CO, 451 ch. 2 CPC, 452 al. 2 CPC